Academic Writing Class’ Perceptions of Portfolios Assessment - Tera Athena (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2016)
Using portfolio as a academic writing assessment has been applied in the last semester. For the following action this paper investigates the students opinions as their perceptions and reflections of the portfolios assessment that has been applied in academic writing I. The data have been obtained from semi-structured interviews with 10 students English Department who took Academic Writing I. The qualitative research design was administered to analyze the data by identifying and classifying the contents of student’ opinion and reflections toward portfolio assessment that has been implemented in Academic Writing I. The investigation found that most of students encouraged the implementation of portfolios assessment, the students cited that the portfolio gives a positive reward to the students’ writing. They felt portfolio assessment can build the objective assessment. Thus, it is recommend to keep using portfolios to assess the students’ composition. And also the improvement of portfolio is needed that is e-portfolios in academic writing assessment.